Optimization of GA3 and row ratio for seed yield of a promising hybrid rice variety - Hasan, MJ; Rahman, MH; Akter, A; Kulsum, MU (Bangladesh Journal of Botany, 2018)
GA3 application at the rate of 225 g/ha with 12 rows of cytoplasmic male stenile (CMS) line and two rows of restorer lines appeared to be the optimum for highest yield of rice. This combination found results of per out crossing rate (OCR) (3.29 t/ha) for F1 seed production.